Controllable Synthesis of Crystalline ReS2(1−x)Se2x Monolayers on Amorphous SiO2/Si Substrates with Fast Photoresponse. Issue 4 (20th December 2019) - Kang, Peipei; Nan, Haiyan; Zhang, Xiumei; Mo, Haoxin; Ni, Zhenhua; Gu, Xiaofeng; Ostrikov, Kostya (Ken); Xiao, Shaoqing
Abstract: Re‐based transition metal dichalcogenides (TMDs) and alloys have many unusual features such as in‐plane anisotropic optical, electrical, and phonon properties and thus receive increasing research interest. However, the distorted 1T structure and the weaker interlayer coupling easily cause anisotropic growth and out‐of‐plane growth, making it particularly challenging to produce Re‐based TMD and alloy monolayers on amorphous SiO2 /Si substrates. Here, a reliable method is developed for the synthesis of high‐quality and large‐size ReS2(1− x ) Se2 x monolayer crystals on SiO2 /Si substrates by NaCl‐assisted, confined‐space chemical vapor deposition. The synergy of salt assistance with the confined reaction space facilitates the formation of intermediate metal oxychlorides and creates a relatively stable growth environment, finally leading to the successful synthesis of ReS2(1− x ) Se2 x monolayer crystals on SiO2 /Si substrates. The as‐grown ReS2(1− x ) Se2 x monolayer alloys exhibit continuously variable composition, high crystal quality, and uniform distribution of Re, S, and Se elements. Furthermore, the ReS2(1− x ) Se2 x based photodetectors display good photoresponse to visible and near‐infrared light with a fast response of less than 15 ms. The salt‐assisted, confined‐space chemical vapor deposition provides a reliable way for the synthesis of large‐scale low‐lattice symmetry 2D materials on amorphous SiO2 /Si substrates and opens up new prospects for Re‐based TMDs and alloys in optoelectronic devices. Abstract : High‐quality and large‐size ReS2(1− x ) Se2 x monolayer films are prepared on amorphous SiO2 /Si substrates by a controllable and reliable method that synergizes the effects of common salt (NaCl) and confined‐space synthesis in a versatile and scalable chemical vapor deposition process. The ReS2(1− x ) Se2 x based photodetectors exhibit good photoresponse to visible and near‐infrared light with a fast response of less than 15 ms.